A Framework for Urban Transport Projects : Operational Guidance for World Bank Staff - Mitric, Slobodan (World Bank, Washington, DC, 2014)
This paper starts with a brief perspective on urban transport in developing countries, followed by a detailed presentation of an overall framework for making projects in this sector. Additional details on cities and projects used as case studies are given in the accompanying tables. The challenge for the Bank is to assist client cities in providing transport infrastructure and services that respond to demographic, spatial and economic growth in ways that balance the many different competing interests. Reflecting the importance that poverty and environmental factors are given in its development lending, the key strategic goal of the Bank is to protect and nurture public transport services and non-motorized transport modes, with underlying meta-objectives of equity and sustainability. In the policy dimension, the following approach features: (i) the equitable allocation of existing/new street space to protect and nurture public transport, and non-motorized modes; (ii) a for-the market rather than in the market, on the street competitive model for public transport, with services operated by the private sector under strong public regulation, and oversight; (iii) a financially viable public transport system, with affordable fares commensurate with costs, and any necessary subsidies targeted to those in need; (iii) appropriate user charges for urban roads (parking and traffic); and (iv) feedback from transport demand to resource mobilization from within the sector. The investment dimension of the approach is increasingly oriented towards the provision and rehabilitation of public transport systems operating on exclusive rights of way, both roadway and rail-based, because of their potential for efficient, high-quality services as well as for being a vehicle for progress on several policy fronts. The final chapter illustrates a variety of ways in which this framework is reflected in the design of actual Bank-funded urban transport projects.